Effect of dexmedetomidine combined with the modified Trendelenburg position on intraocular pressure in patients undergoing robot-assisted laparoscopic surgery: A randomized controlled trial - Shuyang Yan; Jindong Liu; Beibei Xiao; Chunyan Guo; Binghan Wang; Runhan Shi; Qian Deng (PLoS ONE, 2026)
Objective This study aimed to evaluate the effect of combining dexmedetomidine infusion with a modified Trendelenburg position on intraocular pressure (IOP) in patients undergoing robot-assisted laparoscopic surgery (RALS). Methods In a single-center, prospective, 2 × 2 factorial randomized controlled trial, 160 patients scheduled for RALS were allocated to one of four groups: control (normal saline + traditional position), modified position alone, dexmedetomidine alone, or the combination of both. IOP was measured at baseline, during key surgical phases, and after extubation. The primary outcome was IOP during surgery. Secondary outcomes included the incidence of cardiovascular adverse events and the requirement for vasoactive drugs. Results A total of 153 patients completed the study protocol. Both dexmedetomidine and the modified position significantly reduced IOP during surgery (main effect of drug: F = 35.2, P < 0.001; main effect of position: F = 28.7, P < 0.001). Critically, a statistically significant interaction was observed between the two interventions (F = 4.8, P = 0.030), indicating a synergistic effect. The combination group demonstrated the greatest reduction in IOP from time points T2 to T4, ranging from 3.6 to 4.8 mmHg lower than the control group. There were no significant differences in the overall incidence of adverse events among the groups. Conclusions In conclusion, for patients undergoing prolonged robotic laparoscopic surgery (with a mean operative time of 217 minutes), the combined use of dexmedetomidine infusion and a modified Trendelenburg position provides an effective and synergistic strategy for intraocular pressure control. This approach offers a practical means to enhance intraoperative ocular safety during such lengthy procedures. Trial registration Chinese Clinical Trial Registry ChiCTR2300072961